Discovery of clocinizine as a potential oral drug against Schistosoma mansoni infection - Thalitta Castro; Thainá R. Teixeira; Mariana Siegl; Flávia B. Lopes; Maria Cristina C. Espírito-Santo; João Paulo S. Fernandes; Josué de Moraes (Scientific Reports)
Abstract Schistosomiasis, a disease caused by parasitic worms, imposes a significant global health burden, affecting over 240 million people, particularly in low-income regions. To meet the Sustainable Development Goals (SDG), the World Health Organization (WHO) emphasize the need for novel antischistosomal agents. In previous work we identified that cinnarizine, a first-generation antihistamine, has promising antischistosomal activity. This study investigates the therapeutic potential of clocinizine, a chlorinated analogue of cinnarizine, against Schistosoma mansoni. Both in vitro and in vivo studies were conducted to assess its efficacy and compare it to the standard-of-care drug, praziquantel. Clocinizine exhibited potent in vitro antiparasitic activity, with an EC50 of 4.6 µM against adult worms. In a murine model of schistosomiasis, a single oral dose of 400 mg/kg clocinizine salt significantly reduced both worm burden and egg production by 86% and 89%, respectively. These results were comparable to the efficacy of praziquantel at 400 mg/kg, which achieved a 90% reduction in worm burden and an 84% reduction in egg counts. These findings underscore the potential of clocinizine as a promising antischistosomal agent and offer valuable insights for the development of novel cinnarizine-derived compounds with improved selectivity and efficacy.